A foreign subsidiary's largest shareholder, entry mode, and divestitures: The moderating role of foreign investment inducement policies - Jongpil Park; Woojin Yoon (European Research on Management and Business Economics (ERMBE), 2022)
This study investigates the relationships among the influence of the largest shareholder, the entry mode of foreign direct investment companies in Korea, and subsidiary divestitures to demonstrate how the government's FDI policies can work as a moderator. Using data from 468 foreign manufacturing firms that set up plants in Korea through FDI between 2008 and 2011, a survival analysis was performed using the Cox proportional hazards model. The statistical results suggest that the possibility of foreign subsidiary divestiture increased with the level of influence held by the company's largest shareholder. Also, the entry mode of mergers and acquisitions was more likely than the greenfield entry mode to result in foreign subsidiary divestiture. Lastly, the host country's FDI policies moderate the relationship between the influence of the largest shareholder and foreign subsidiary divestiture.
Keywords: F23; G38; M16; O25; 650; Entry mode; Foreign investment inducement policy; Foreign subsidiary divestiture; Largest shareholder